Unusual Location of Intraperitoneal Fibromyoma: Rarity Does Not Rule Out the Diagnosis (Journal of Chittagong Medical College Teachers' Association, 2020)
Fibromyoma which is commonest benign tumor mostly arises from smooth muscles of uterus present in 20-25% women of reproductive age group. Round ligament Fibromyoma is rare tumor & exact incidence not known. It may mimic ovarian tumor when it was intra peritoneal and located in adnexa. Preoperative diagnosis can be made by history, clinical examination, USG, CT scan of abdomen. Surgical excision is the curative treatment. A 35 years lady para 2 presented with lump in lower abdomen gradually increasing in size for 3-4 yrs and pain for 2 months. On examination firm palpable mass of 28 weeks pregnancy size.  Her USG and CT scan detected well defined 28 cm x 22 cm X 20 cm mass in right adnexa & diagnosis given ovarian tumor. Her CA 125 level was 97unit/ml. Laparotomy finding was a big firm lobulated tumor arises from right round ligament. Tumor removed as a whole, uterus, both ovaries, and left sided fallopian tube healthy & preserved. Final histopathological diagnosis benign fibromyoma with degenerative change. So diagnosis of fibromyoma always kept in mind during the differential diagnosis of any pelvic mass.JCMCTA 2020 ; 31 (1) : 130-133